Analysing cost of hospital care to a family with an extreme preterm neonate. Issue 2 (April 2020) - Gurram Venkata, Sujith Kumar Reddy; Pournami, Femitha; Alok, Kumar MK; Nandakumar, Anand; Prabhakar, Jyothi; Jain, Naveen
Abstract: Background and objective: Reports on expenses to families of extreme preterm babies are scarce. Charges may vary based on regional socio-economic conditions. Systematic auditing of hospital care costs helps families develop a tangible feel of expected expenses. It also allows the medical team to identify areas where costs can be reduced. We studied expenses borne by the families towards care of an extreme preterm neonate during hospital stay. Methods: Neonates who were delivered <28 weeks and who completed care till discharge in the unit were included. The bills to the family were retrospectively analysed. Results: The median per day charge borne by the family was USD 107.4 (IQR 94.6–135.5). The median total cost to the patient was USD 9446.5. Maximum proportion of the costs were towards nursing charges. Conclusions: The average per day charges was USD 107.4 (IQR 94.6–135.5). Stringent efforts should be made by the health care teams to optimise the costs to families. Neonatal intensive care needs to be commercially viable as well.